Hubungan antara Perhatian Orang Tua dengan Budi Pekerti Remaja di Jorong Usak Alahan Panjang Kecamatan Lembah Gumanti Kabupaten Solok - Yulianti Yulianti; Syuraini Syuraini (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2018)
Background of this research is character of teens in Usak Alahan Panjang Kecamatan Lembah Gumanti Kabupaten Solok stil low. This is suspected because parents attention is stil low. The type of this reseach is to description 1) the attention of parents to adolescents, (2) the character of teenagers, and (3) to see whether there is a relationship between parents' attention and youth character in Jorong Usak. Population in this research is 40 people. The technique use for taken sampling is Stratified random sampling as much as 80% of adolescents. Samples in this research was 32 parents. Data collection techniques used were questionnaires, while data collection tools used questionnaires. Technique of data analysis by using formula of percentage and product moment. The result of the research is the attention given by the parents to the children in Jorong Usak Alahan Panjang Kecamatan Lembah Gumanti Solok Regency in the low category, adolescent character in the category is very low, and there is a significant correlation between the attention of the parents to the youth character in Jorong Usak Alahan Panjang Kecamatan Lembah Gumanti Solok District. Suggestions in this study is to parents to need to improve understanding, knowledge, and improve about the attention to adolescents, so that adolescents can show good behavior.Keywords: Parent Attention, Character